2019
DOI: 10.1007/s10029-019-01928-6
|View full text |Cite
|
Sign up to set email alerts
|

Is round ligament varicosity in pregnancy a common precursor for the later development of inguinal hernias? The prospective analysis of 28 patients over 9 years

Abstract: Purpose Short-term effects of round ligament varicosity (RLV) in pregnancy have been investigated in small-scale studies. The long-term effects are unknown. This study aims to evaluate the risk of groin hernia manifestation after RLV in pregnancy, to delineate possible risk factors and to analyze the natural course of pregnancy and post-partum period with regard to RLV. Methods In a prospective analysis 28 pregnant women with RLV presented to the hernia clinic over 9 years. After clinical and ultrasound examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
(15 reference statements)
0
10
0
1
Order By: Relevance
“…Mesh placement has been shown, even in small ventral hernias with fascial defect <2 cm, to reduce likelihood of recurrence especially during subsequent pregnancy but is associated with higher chance of chronic post‐operative pain 13 and post‐operative wound infection. Others suggest that mesh placement is not associated with significant impact on subsequent pregnancies and labour course itself 14,15 . Our standard practice is mesh placement in large umbilical or paraumbilical hernias larger than 2 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Mesh placement has been shown, even in small ventral hernias with fascial defect <2 cm, to reduce likelihood of recurrence especially during subsequent pregnancy but is associated with higher chance of chronic post‐operative pain 13 and post‐operative wound infection. Others suggest that mesh placement is not associated with significant impact on subsequent pregnancies and labour course itself 14,15 . Our standard practice is mesh placement in large umbilical or paraumbilical hernias larger than 2 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Watchful waiting is accepted in case of an asymptomatic reducible groin mass based on RLVs. Postpartum, when pelvic venous obstruction by the gravid uterus is relieved, spontaneous resolution occurs in most patients [78]. In case of a symptomatic reducible groin mass, duplex sonography is advised, as it helps in differentiating RLV from other causes of inguinal swelling in pregnancy, thus avoiding unnecessary surgical exploration [73,79].…”
Section: Reproductive Potentialmentioning
confidence: 99%
“…Regarding groin hernia during pregnancy, it does not require routine repair [14]. Round ligament varicosities (RLV) are a common differential diagnosis of groin hernia, and they usually disappear within two to four weeks after delivery [15]. The recurrence rate of ventral hernias in women of reproductive age is about 12% [12].…”
Section: Determining the Best Time For Elective Surgerymentioning
confidence: 99%
“…However, another study revealed that mesh repair was not associated with a reduction in the recurrence risk [26]. The mesh repair of ventral hernia and inguinal hernias appears to be a safe approach with no significant impact on pregnancy and labor course [15,24,27]. During pregnancy, suture repair may increase the risk of recurrence.…”
Section: Suture Versus Mesh Repairmentioning
confidence: 99%